A storm of opinions on Brexit referendum

(untitled) (Département des littératures de langue française, 2016)
June 23rd, 2016 Brexit referendum will have incalculable consequences. It may be surprising to see Britain leaving the European Union while UK negotiated some advantageous positions. But a referendum is a risky bet : it allows all opponents to add their voices while the Remaining Campaigns had to gather many people who were not ready to give David Cameron a carte blanche (This aspect also explains why Scots could vote for Europe, as their vote was clearly not backing Cameron). Whatever will be happening, this vote is a great victory for populism in Europe. Clairvoyance is urgently needed from the European leaders to relaunch a continental dynamics after this disavowal.